Genetic background of high blood pressure is associated with reduced mortality in premature neonates. Issue 2 (14th June 2019) - Göpel, Wolfgang; Müller, Mirja; Rabe, Heike; Borgmann, Johannes; Rausch, Tanja K; Faust, Kirstin; Kribs, Angela; Dötsch, Jörg; Ellinghaus, David; Härtel, Christoph; Roll, Claudia; Szabo, Miklos; et al.
Abstract : Objective: The aim of our study was to determine if a genetic background of high blood pressure is a survival factor in preterm infants. Design: Prospective cohort study. Setting: Patients were enrolled in 53 neonatal intensive care units. Patients: Preterm infants with a birth weight below 1500 g. Exposures: Genetic score blood pressure estimates were calculated based on adult data. We compared infants with high genetic blood pressure estimates (>75th percentile of the genetic score) to infants with low genetic blood pressure estimates (<25th percentile of the genetic score). Main outcome measures: Lowest blood pressure on the first day of life and mortality. Results: 5580 preterm infants with a mean gestational age of 28.1±2.2 weeks and a mean birth weight of 1022±299 g were genotyped and analysed. Infants with low genetic blood pressure estimates had significantly lower blood pressure if compared with infants with high genetic blood pressure estimates (27.3±6.2vs 27.9±6.4, p=0.009, t-test). Other risk factors for low blood pressure included low gestational age (−1.26 mm Hg/week) and mechanical ventilation (−2.24 mm Hg, p<0.001 for both variables, linear regression analysis). Mortality was significantly reduced in infants with high genetic blood pressure estimates (28-day mortality: 21/1395, 1.5% vs 44/1395, 3.2%, p=0.005, Fisher's exact test). This survival advantage was independent of treatment with catecholamines. Conclusions: Our study provides first evidence that a genetic background of high blood pressure may be beneficial with regard to survival of preterm infants.